Diagnostic ergonomique résultant de la présence de risques psychosociaux contribuant aux troubles musculo-squelettiques : le cas des centres d’appels d’urgence 9-1-1 - Georges Toulouse; Louise St-Arnaud; Denis Duhalde; Julie Lévesque; Alain Delisle; Alain-Steve Comtois (Perspectives Interdisciplinaires sur le Travail et la Santé)
Few ergonomic research interventions have as yet been published regarding the association between psychosocial risks and musculoskeletal disorders (MSDs). This paper begins with an overview of the intervention methods in this field, and then presents the choice of a diagnostic model used to conduct interventions in 911 emergency call centers. This model is based on an analysis of mental and emotional loads. Their relation with the MSDs and stress are examined by administering perception scales, an EMG of the trapezius muscle, and the loss of cardiac rhythm variability. A self-analysis interview was conducted to document high-load situations related to the organizational context. The results allowed us to outline the interest and limitations of this diagnostic approach.